Chronic electromyograms in treadmill running SOD1 mice reveal early changes in muscle activation - Quinlan, Katharina A. (J Physiol, 2017)
KEY POINTS: The present study demonstrates that electromyograms (EMGs) obtained during locomotor activity in mice were effective for identification of early physiological markers of amyotrophic lateral sclerosis (ALS). These measures could be used to evaluate therapeutic intervention strategies in animal models of ALS. Several parameters of locomotor activity were shifted early in the disease time course in SOD1G93A mice, especially when the treadmill was inclined, including intermuscular phase, burst skew and amplitude of the locomotor bursts. The results of the present study indicate that early compensatory changes may be taking place within the neural network controlling locomotor activity, including spinal interneurons. Locomotor EMGs could have potential use as a clinical diagnostic tool. ABSTRACT: To improve our understanding of early disease mechanisms and to identify reliable biomarkers of amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disease, we measured electromyogram (EMG) activity in hind limb muscles of SOD1G93A mice. By contrast to clinical diagnostic measures using EMGs, which are performed on quiescent patients, we monitored activity during treadmill running aiming to detect presymptomatic changes in motor patterning. Chronic EMG electrodes were implanted into vastus lateralis, biceps femoris posterior, lateral gastrocnemius and tibialis anterior in mice from postnatal day 55 to 100 and the results obtained were assessed using linear mixed models. We evaluated differences in parameters related to EMG amplitude (peak and area) and timing (phase and skew, a measure of burst shape) when animals ran on level and inclined treadmills. There were significant changes in both the timing of activity and the amplitude of EMG bursts in SOD1G93A mice. Significant differences between wild‐type and SOD1G93A mice were mainly observed when animals locomoted on inclined treadmills. All muscles had significant effects of mutation that were independent of age. These novel results indicate (i) locomotor EMG activity might be an early measure of disease onset; (ii) alterations in locomotor patterning may reflect changes in neuronal drive and compensation at the network level including altered activity of spinal interneurons; and (iii) the increased power output necessary on an inclined treadmill was important in revealing altered activity in SOD1G93A mice.